Acute hepatitis B in pregnancy with surprisingly rapid clearance of serum HBs antigen associated with a favourable outcome. (May 2022) - Roger, Steven; Fontana, Julien; Ducancelle, Alexandra; Le Guillou-Guillemette, Hélène; Canivet, Clémence M; Lefeuvre, Caroline
Highlights: HBsAg seroclearance may vary according to the precore/core mutations. HBsAg seroclearance may vary according to the hepatitis B virus (HBV) genotype. Pregnancy might be a risk factor for chronicity following acute HBV infection. Antiviral drugs in cases of acute hepatitis B (AHB) in pregnancy may prevent progression to chronicity. Abstract: Acute hepatitis B (AHB) is usually asymptomatic, but it can progress to chronic hepatitis B (HB) defined by HB surface antigen (HBsAg) persisting beyond 6 months. Nevertheless, the delay of HBsAg seroclearance is not well-defined. During pregnancy, the immune system of the pregnant women is altered and delayed HBsAg loss can be observed, leading to chronic infection. Here, we present an uncommon case of AHB in a pregnant woman in whom rapid HBsAg seroclearance (52 days after AHB) was associated with a favourable outcome (no injury to liver). This patient received tenofovir disoproxil fumarate promptly after diagnosis. The case raises questions about the use of antiviral treatment in AHB. This is generally not recommended in AHB, but it would be potentially useful in pregnant women to reduce the risk of chronic HB infection and could also prevent the transmission of the maternal precore mutation, thus reducing the significant risk of fulminant hepatitis in the infant. This case also highlights the impact of the hepatitis B virus (HBV) genotype and precore/core mutations on the clinical course of the disease.